Homogeneous-heterogeneous reactions in carbon nanotubes over a stretching sheet - Lokman, Ahmad Danial; Bachok @ Lati, Norfifah; Rosali, Haliza (Universiti Putra Malaysia Press, 2019)
The heat transfer and the effects of homogeneous-heterogeneous reactions on the steady boundary layer flow of carbon nanotubes (CNTs) over a stretching sheet is discussed. The governing partial differential equations and boundary conditions are transformed into a set of nonlinear ordinary differential equations by using suitable similarity transformations. There are two types of CNTs used which are SWCNTs and MWCNTs with three different types of base fluids which are water, kerosene and engine oil. These equations are then solved numerically by Maple software using shooting method. The effects of the governing parameters on the dimensionless velocity, temperature, concentration, skin friction and Nusselt numbers are analyzed and presented in graphical forms. It is found that as the homogeneous-heterogeneous reactions decreases the concentration distribution getting increase, and volume fraction parameter as well as the suction parameter will effect the fluid flow.